Critical Pedagogy and Assessment of Educational Inclusion - Fatma Sabri; Nawal Benmostfa (The Journal of Studies in Language, Culture and Society, 2019)
The desire to create a system where students with special needs receive their education in the general education classroom with non-disabled students is the kind of a critical pedagogy within the educational paradigm. Inclusion does not refer to a physical space it rather refers to a condition or state of being; ‘the concept of inclusion implies a sense of belonging and acceptance. ’ Supported education for inclusion emphasizes that successful inclusion hinges on provision of appropriate supports in the general educational classroom as a basis for establishing a successful learning environment for students. Inclusion is the responsibility of every teacher and every school leader to learn the strategies necessary to make inclusive education possible.